UNJUK KERJA TEKNIK PENYARADAN KAYU DENGAN METODE TREE LENGTH LOGGING PADA HUTAN ALAM LAHAN KERING - Maman Mansyur Idris; Soenarno (BRIN Publishing, 2015)
In Indonesia, logging in natural forests is generally undertaken by cutting the main trunk along the clear boles and skidding the trunk to the landing point. This paper examines skidding performance of an alternative method, i.e. tree length logging which conducted by cutting off the stem above the first branch up to minimum diameter of 20 cm, which is manifested by the productivity and skidding cost. The method was practiced in four areas of Licency Natural Forest Concessionary managed by intensive sylvicultural system. Results show that the log skidding productivity ranged from 21.127 – 23.893 m³/hour with average of 22.217m³/hour depending on skidding distance. Meanwhile, skidding cost of tree length method ranged from Rp 24,852.36 - Rp 29,318.49/m³ with average of Rp 28,628.10/m³ with skidding distance ranged from 100 m to 225 m.